Divine art, infernal machine : the reception of printing in the West from first impressions to the sense of an ending - Eisenstein, Elizabeth L. (Material texts., 2011)
'Divine Art, Infernal Machine' presents a history of the printing press & of the ambivalent attitudes of the public toward printers & printing since the days of Gutenberg & his business partner Johann Fust, a gentleman often tellingly confused with the notorious Doctor Faustus.